Bioaccumulation of hexavalent chromium in lettuce (Lactuca sativa L.) and Swiss chard (Beta vulgaris var. cicla) - Pedro Escudero‐Villa; Jéssica Núñez‐Sánchez; Leslie Núñez‐Sánchez; Diego Silva‐Merchán; Jenny Paredes‐Fierro (Urban Agriculture & Regional Food Systems)
Abstract The presence of chemical agents in natural systems and crops is alarming for the people's health due to the consumption of vegetables that, in some cases, absorb heavy metals (cadmium, copper, chromium, etc.). Hexavalent chromium (Cr6+) prevails under oxidation conditions and depends on the pH of the solution, being able to form additional species. The toxic characteristics of Cr6+ motivate our interest in evaluating the presence of this heavy metal in two species, lettuce (Lactuca sativa L.) and Swiss chard (Beta vulgaris var. cicla). Experiments were performed in two phases: the first phase for seed germination and the last for early growth plants. Germination was determined over 120 h and early plant growth was determined in the greenhouse. Chromium accumulation and plant tissue morphology and color were analyzed with a bifactorial analysis of variance for each plant species. Lettuce and Swiss chard germination were 90% and 30%, respectively, at the highest Cr6+ concentration of 8 ppm. However, root length was 41.6% for lettuce and 38% for Swiss chard at 8 ppm, indicating moderate phytotoxicity when compared with previous studies. The bioaccumulation capacity of the two species makes them suitable for bioremediation alternatives for small crops. Additionally, the depigmentation in aerial parts may serve as a guide to identify the potential presence of Cr6+ in the plants in the early stages of growth, preventing consumption.